Catalyst for treating VOCs by catalytic oxidation at room temperature, preparation method and application thereof
By preparing a normal temperature catalytic oxidation catalyst composed of activated carbon, activated metal salt and 2-thiazolylamine, the problem of high energy consumption when treating low-concentration VOCs exhaust gas at room temperature in the prior art is solved, and the VOCs degradation effect with high efficiency and low energy consumption is achieved.
Patent Information
- Application Number
- CN202310001805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-01-03
AI Technical Summary
In the prior art, when handling chemical equipment on-site maintenance, packaging and filling waste gas, the organic substance concentration itself requires high energy consumption, and how to achieve the degradation of low concentration VOCs at room temperature has become a key issue.
A method of preparing a normal temperature catalytic oxidation catalyst is adopted. Catalysts with high catalytic activity and stability are prepared by grinding activated carbon into fine powder and sonicating with alcohol liquid, combined with low-temperature vacuum impregnation and ultrasonic assistance. The catalyst consists of the support activated carbon, activated metal salt and 2-thiazolylamine, and is extruded by mixing the binder and water, and calcining in two stages.
It realizes efficient degradation of low-concentration VOCs at room temperature, significantly reducing energy consumption, and simple and easy to use process, wide application range, and can effectively reduce secondary pollution.
Smart Images

Figure BDA0004034240180000111 
Figure BDA0004034240180000121 
Figure HDA0004034240190000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of industrial waste gas treatment and environmental protection catalytic materials, and in particular to a catalyst for treating VOCs by catalytic oxidation at room temperature, a preparation method and application thereof. Background Art
[0002] In recent years, the haze problem in my country has become increasingly serious, seriously affecting human health and the harmonious development of society. Haze is mainly caused by high concentrations of aerosols in the atmosphere, including a large amount of organic aerosols, and volatile organic compounds (VOCs) are important precursors to the formation of organic aerosols. A large amount of VOCs will be generated in the petrochemical, coal chemical, oil storage, transportation and sales processes, as well as the production and use of coatings, inks, adhesives, etc. Therefore, it is urgent to strengthen the research and demonstration application of industrial organic waste gas treatment technology.
[0003] At present, the main treatment methods for volatile organic compounds include adsorption, absorption, combustion, condensation, low-temperature plasma oxidation, biological purification, photocatalytic technology, etc. Among them, the most promising VOCs treatment technology is catalytic oxidation technology. Due to the economic and technical advantages of catalytic oxidation, researchers have been committed to the research of high-performance catalysts in the catalytic oxidation process. However, for on-site maintenance waste gas of chemical equipment, packaging and filling storage waste gas, odorous waste gas, etc., since the organic matter concentration itself is extremely low and basically has no calorific value, the use of catalytic oxidation requires high energy consumption. How to achieve the degradation of low-concentration VOCs at room temperature is particularly critical. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a catalyst for catalytic oxidation treatment of VOCs at room temperature, a preparation method and application.
[0005] The first object of the present invention is to provide a room temperature catalytic oxidation catalyst. The catalyst has high catalytic activity and stability, can significantly reduce the catalytic conversion temperature of VOCs, and achieve effective treatment of VOCs with low energy consumption.
[0006] The second object of the present invention is to provide a method for preparing the catalyst.
[0007] The third object of the present invention is to provide a method for using the catalyst to treat VOCs waste gas at room temperature. The treatment method is simple and easy to implement, has a wide range of applications, can effectively treat low-concentration VOCs, and effectively reduce secondary pollution.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] In one aspect, the present invention provides a method for preparing a catalyst for treating VOCs by catalytic oxidation at room temperature, comprising the following steps:
[0010] 1) Grinding the activated carbon into fine powder and sieving it, adding the sifted powder into an alcohol solution, and ultrasonically treating it to obtain a carrier dispersion;
[0011] 2) adding the 2-thiazolamine solution to the active metal salt solution and subjecting the solution to ultrasonic treatment to obtain a precursor mixed solution;
[0012] 3) adding the precursor mixture to the carrier dispersion and performing low-temperature vacuum impregnation, assisted by ultrasound, filtering after the impregnation, and performing two-stage calcination to obtain a powder catalyst;
[0013] 4) Add a binder and water to the powder catalyst, mix well, extrude and shape, and calcine in two stages to obtain a room temperature catalytic oxidation catalyst.
[0014] The carrier of the present invention is a traditional steam-activated activated carbon, which has a large specific surface area and a loose porous structure. At the same time, because its pH is neutral, the active metal is not easy to fall off, and it is very suitable for use as a catalyst carrier.
[0015] Furthermore, the mesh number of the sieving in step 1) is 100-200 mesh, the alcohol solution is one or more of ethanol, ethylene glycol and propylene glycol, the mass ratio of the sieved powder to the alcohol solution is 1:(1-2), and the ultrasonic conditions of the ultrasonic treatment are: the ultrasonic frequency is 80-120 Hz, and the ultrasonic treatment time is 1-2h.
[0016] Furthermore, in the step 2), the active metal salt solution is one or both of nickel and copper salt solutions, and the nickel salt and copper salt are selected from nickel nitrate, nickel chloride, copper nitrate and copper chloride;
[0017] Preferably, the active metal salt solution in step 2) uses nickel nitrate and copper nitrate, and the concentration of the metal salt solution is based on metal concentration. The concentration of nickel nitrate solution is 1-3wt%, preferably 1.5-2wt%, and the concentration of copper nitrate solution is 1-4wt%, preferably 2-3wt%; the mass amount of the active metal salt solution in step 2) is 0.2-0.8 times the mass of the activated carbon fine powder.
[0018] The concentration of the 2-thiazolamine solution is 1-2 wt% (calculated as nitrogen element), and the amount of the 2-thiazolamine solution is the mass ratio of the solution to the activated carbon fine powder, which is (0.001-0.004):1.
[0019] The ultrasonic conditions in step 2) are: ultrasonic frequency is 80-120 Hz, and ultrasonic treatment time is 1-2 h.
[0020] In the present invention, the mass ratio of the precursor mixed liquid to the carrier dispersion liquid in step 3) is (0.067-0.402):1.
[0021] Furthermore, the conditions of the low-temperature vacuum impregnation described in step 3) are: impregnation time 1 to 2 hours, temperature controlled at 0 to 5°C, vacuum pressure 2 to 10 kPa, inert gas added once every 20 minutes to normal pressure, the inert gas is preferably nitrogen; the ultrasonic frequency is 80 to 120 Hz. The calcination atmosphere in the calcination process is an inert gas atmosphere, preferably nitrogen, the first calcination temperature is 150 to 250°C, preferably 180 to 220°C, the calcination time is 3 to 5 hours, the heating rate is 5°C / min, the second calcination is 450°C to 650°C, preferably 500°C to 600°C, and the heating rate is 5°C / min.
[0022] Low-temperature impregnation effectively prevents the aggregation of active metals, allowing them to be effectively dispersed. Vacuum impregnation can effectively expel the gas molecules that occupy the pores of activated carbon, which is beneficial for the pores to be occupied by active metals.
[0023] Furthermore, the mixing ratio in step 4) is a mass ratio of powder catalyst: binder: water = 1: (0.01-0.1): 0.05, preferably 1: (0.03-0.05): 0.05, the calcination atmosphere is an inert gas atmosphere, preferably nitrogen, the calcination temperature in the first stage is 150-250°C, preferably 180-220°C, the calcination time is 3-5h, the heating rate is 5°C / min, and the second stage is 300°C-450°C, preferably 350°C-400°C, and the heating rate is 5°C / min.
[0024] In the present invention, the binder in step 4) is selected from carboxymethyl cellulose. By adding the binder and extruding, the strength of the catalyst is greatly improved, so that the catalyst maintains better stability under gas-liquid impact.
[0025] On the other hand, the present invention provides a catalyst for treating VOCs by catalytic oxidation at room temperature prepared by the above method.
[0026] In a third aspect, the present invention further provides an application of the catalyst of the present invention to catalytically oxidize and treat VOCs waste gas at room temperature, and the process route is as follows:
[0027] The catalyst is loaded into the reactor to control the VOCs concentration of the exhaust gas to less than 300 mg / m 3 , preferably <200 mg / m 3 , airspeed 500~4000h -1 , preferably 1000~2000h -1 Entering into the reactor, reacting at 0-60°C, preferably 20-40°C;
[0028] VOCs waste gas enters the reactor and contacts the cross-flowing hydrogen peroxide or sodium hypochlorite solution in the catalyst layer. The active components such as nickel and copper in the catalyst decompose hydrogen peroxide or sodium hypochlorite to produce strong oxidizing hydroxyl radicals (·OH). ·OH oxidizes and degrades VOCs molecules, and the degraded waste gas is discharged. The concentration of oxidant H2O2 is controlled at 0.2% to 0.4%, the concentration of NaClO at 0.3% to 0.6%, and the liquid-gas ratio is required to be ≥2L / m 3 , the pH of the aqueous phase is controlled at 9-11;
[0029] In the application method of the present invention, VOCs waste gas can be treated by catalytic oxidation at room temperature in any reactor known in the art, preferably a fixed bed reactor, and more preferably a tower device.
[0030] The positive effects of the present invention are:
[0031] 1) Using activated carbon to synthesize room temperature catalytic oxidation catalysts to increase the specific surface area and porous structure of the catalyst, which is beneficial for the catalyst to capture VOCs molecules;
[0032] 2) The low-temperature vacuum impregnation process effectively improves the dispersion of active metals, and the nitrogen doping ensures that the metals are not easy to cluster at extremely high dispersion. The sulfur doping reduces the desorption energy barrier of VOCs in the activated carbon pores, thereby improving the stability of catalyst operation.
[0033] 3) The VOCs treatment process of the present invention is simple, the reaction temperature is mild, the energy consumption is extremely low, and it has the prospect of wide-range application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Process flow chart DETAILED DESCRIPTION
[0035] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0036] In the following specific implementation of the present invention:
[0037] Activated carbon was from Jiangsu Zhuxi Activated Carbon Co., Ltd.;
[0038] 27.5wt% hydrogen peroxide came from Wanhua UT water system;
[0039] Sodium hypochlorite solution comes from the byproduct of Wanhua's HCl oxidation unit;
[0040] The room temperature catalytic oxidation tower was purchased from Huada Medical Instrument Co., Ltd.;
[0041] VOCs waste gas was prepared with cylinder gas, which was a single component of butyl acetate with a mass concentration of 10,000 ppm. It was purchased from Yantai Shuangfeng Gas Company and used after dilution.
[0042] The specific surface area was measured by a V-Sorb-2800S specific surface area meter produced by Beijing Jin'ep Technology Co., Ltd.
[0043] The concentration of VOCs was analyzed by gas chromatography, and the gas chromatograph was Agilent 7890B produced by Agilent.
[0044] Example 1
[0045] (1) Grind the activated carbon into fine powder and pass it through a 100-mesh sieve. Take 200 g of the fine powder and add it to 200 g of ethanol. Ultrasonicate at 120 Hz for 2 h to obtain a carrier dispersion.
[0046] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 1.5 wt% and 2.5 wt% respectively, taking 60 g of the mixed salt solution, adding 20 g of a 1.2 wt% 2-thiazolamine solution thereto, and ultrasonicating at 120 Hz for 2 h to obtain a precursor mixed solution;
[0047] (3) Add the precursor mixture to the carrier dispersion, immerse at 0°C and 10Kpag for 1 hour, use 120Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 220°C, the calcination time is 3 hours, the second calcination temperature is 550°C, the calcination time is 5 hours, all calcined in a nitrogen atmosphere, the heating rate is 5°C / min, to obtain a powder catalyst;
[0048] (4) Take 200g of powdered catalyst, add 7g of carboxymethyl cellulose and 10g of water, mix evenly, extrude into shape, and then carry out secondary calcination. The primary calcination temperature is 220°C, the calcination time is 3h, and the secondary calcination temperature is 370°C, the calcination time is 5h. Both calcinations are carried out under nitrogen atmosphere with a heating rate of 5°C / min to obtain catalyst 1#.
[0049] Example 2
[0050] (1) Grind the activated carbon into fine powder and pass it through a 120-mesh sieve. Take 200 g of the fine powder and add it to 250 g of ethanol. Ultrasonicate for 1.5 h at 110 Hz to obtain a carrier dispersion.
[0051] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 1.8 wt% and 2.7 wt% respectively, taking 100 g of the mixed salt solution, adding 40 g of a 2 wt% 2-thiazolamine solution thereto, and ultrasonicating for 1.5 h under 110 Hz ultrasonic conditions to obtain a precursor mixed solution;
[0052] (3) Add the precursor mixture to the carrier dispersion, immerse at 2°C and 8Kpag for 1.5 hours, use 110Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 190°C, the calcination time is 4 hours, the second calcination temperature is 600°C, the calcination time is 4 hours, both calcination is carried out in a nitrogen atmosphere, and the heating rate is 5°C / min to obtain a powder catalyst;
[0053] (4) Take 200g of powdered catalyst, add 10g of carboxymethyl cellulose and 10g of water, mix evenly, extrude into shape, and then perform secondary calcination. The primary calcination temperature is 190°C, the calcination time is 4h, and the secondary calcination temperature is 400°C, the calcination time is 4h. Both calcinations are performed under a nitrogen atmosphere with a heating rate of 5°C / min to obtain catalyst 2#.
[0054] Example 3
[0055] (1) Grind the activated carbon into fine powder and pass it through a 160-mesh sieve. Take 200 g of the fine powder and add it to 300 g of ethanol. Ultrasonicate at 100 Hz for 1 h to obtain a carrier dispersion.
[0056] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 2.0 wt% and 2.0 wt% respectively, taking 140 g of the mixed salt solution, adding 60 g of a 1 wt% 2-thiazolamine solution thereto, and ultrasonicating under 100 Hz ultrasonic conditions for 1 h to obtain a precursor mixed solution;
[0057] (3) Add the precursor mixture to the carrier dispersion, immerse at 4°C and 6Kpag for 2 hours, use 100Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 200°C, the calcination time is 5 hours, the second calcination temperature is 500°C, the calcination time is 3 hours, all calcined in a nitrogen atmosphere, the heating rate is 5°C / min, to obtain a powder catalyst;
[0058] (4) Take 200g of powdered catalyst, add 6g of carboxymethyl cellulose and 10g of water, mix evenly, extrude into shape, and then perform secondary calcination. The primary calcination temperature is 200°C, the calcination time is 5h, and the secondary calcination temperature is 380°C, the calcination time is 3h. Both calcinations are performed under a nitrogen atmosphere with a heating rate of 5°C / min to obtain catalyst 3#.
[0059] Example 4
[0060] (1) Grind the activated carbon into fine powder and pass it through a 180-mesh sieve. Take 200 g of the fine powder and add it to 350 g of ethanol. Ultrasonicate at 90 Hz for 1.5 h to obtain a carrier dispersion.
[0061] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 1.6 wt% and 3.0 wt%, respectively; taking 40 g of the mixed salt solution, adding 80 g of a 1.5 wt% 2-thiazolamine solution thereto, and ultrasonicating for 1.5 h at 90 Hz to obtain a precursor mixed solution;
[0062] (3) Add the precursor mixture to the carrier dispersion, immerse at 5°C and 4Kpag for 1.5 hours, use 90Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 180°C, the calcination time is 4 hours, the second calcination temperature is 530°C, the calcination time is 4 hours, both calcined in a nitrogen atmosphere, the heating rate is 5°C / min, to obtain a powder catalyst;
[0063] (4) Take 200g of powdered catalyst, add 8g of carboxymethyl cellulose and 10g of water, mix evenly, extrude into shape, and then perform secondary calcination. The primary calcination temperature is 180°C, the calcination time is 4h, and the secondary calcination temperature is 350°C, the calcination time is 4h. Both calcinations are performed under a nitrogen atmosphere with a heating rate of 5°C / min to obtain catalyst 4#.
[0064] Example 5
[0065] (1) Grind the activated carbon into fine powder and pass it through a 200-mesh sieve, then add 200 g of the fine powder to 400 g of ethanol and ultrasonicate it at 80 Hz for 2 h to obtain a carrier dispersion;
[0066] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 1.9 wt% and 2.2 wt% respectively, taking 160 g of the mixed salt solution, adding 20 g of a 1.8 wt% 2-thiazolamine solution thereto, and ultrasonicating at 80 Hz for 2 h to obtain a precursor mixed solution;
[0067] (3) Add the precursor mixture to the carrier dispersion, immerse at 1°C and 2Kpag for 1 hour, use 80Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 185°C, the calcination time is 3 hours, the second calcination temperature is 580°C, the calcination time is 5 hours, all calcined in a nitrogen atmosphere, the heating rate is 5°C / min, to obtain a powder catalyst;
[0068] (4) Take 200g of powdered catalyst, add 6g of carboxymethyl cellulose and 10g of water, mix evenly, extrude into shape, and then carry out secondary calcination. The primary calcination temperature is 185°C, the calcination time is 3h, and the secondary calcination temperature is 390°C, the calcination time is 5h. Both calcinations are carried out under nitrogen atmosphere with a heating rate of 5°C / min to obtain catalyst 5#.
[0069] Comparative Example 1
[0070] (1) Grind the activated carbon into fine powder and pass it through a 160-mesh sieve. Take 200 g of the fine powder and add it to 300 g of ethanol. Ultrasonicate at 100 Hz for 1 h to obtain a carrier dispersion.
[0071] (2) preparing 60 g of 1 wt% 2-thiazolamine solution, and ultrasonicating it at 100 Hz for 1 h to obtain a precursor mixed solution;
[0072] (3) Add the precursor mixture to the carrier dispersion, immerse at 4°C and 6Kpag for 2 hours, use 100Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 200°C, the calcination time is 5 hours, the second calcination temperature is 500°C, the calcination time is 3 hours, all calcined in a nitrogen atmosphere, the heating rate is 5°C / min, to obtain a powder catalyst;
[0073] (4) Take 200 g of the powdered catalyst, add 6 g of carboxymethyl cellulose and 10 g of water, mix well, extrude into shape, and then perform secondary calcination. The primary calcination temperature is 200 ° C. and the calcination time is 5 h. The secondary calcination temperature is 380 ° C. and the calcination time is 3 h. Both calcinations are performed under a nitrogen atmosphere at a heating rate of 5 ° C / min to obtain catalyst D1#.
[0074] Comparative Example 2
[0075] (1) Grind the activated carbon into fine powder and pass it through a 160-mesh sieve. Take 200 g of the fine powder and add it to 300 g of ethanol. Ultrasonicate at 100 Hz for 1 h to obtain a carrier dispersion.
[0076] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 2.0 wt% and 2.0 wt% respectively, taking 140 g of the mixed salt solution, adding 60 g of a 1 wt% 2-thiazolamine solution thereto, and ultrasonicating under 100 Hz ultrasonic conditions for 1 h to obtain a precursor mixed solution;
[0077] (3) Add the precursor mixture to the carrier dispersion, impregnate for 2 h at room temperature (25 ° C) and normal pressure, use 100 Hz ultrasonic assistance, add a stream of nitrogen every 20 min to normal pressure, filter after impregnation, and then calcine the obtained solid twice, the first calcination temperature is 200 ° C, the calcination time is 5 h, the second calcination temperature is 500 ° C, the calcination time is 3 h, all calcined in a nitrogen atmosphere, the heating rate is 5 ° C / min, to obtain a powder catalyst;
[0078] (4) Take 200 g of the powdered catalyst, add 6 g of carboxymethyl cellulose and 10 g of water, mix well, extrude into shape, and then perform secondary calcination. The primary calcination temperature is 200 ° C. and the calcination time is 5 h. The secondary calcination temperature is 380 ° C. and the calcination time is 3 h. Both calcinations are performed under a nitrogen atmosphere at a heating rate of 5 ° C / min to obtain catalyst D2#.
[0079] Comparative Example 3
[0080] (1) Grind the activated carbon into fine powder and pass it through a 160-mesh sieve. Take 200 g of the fine powder and add it to 300 g of ethanol. Ultrasonicate at 100 Hz for 1 h to obtain a carrier dispersion.
[0081] (2) preparing a mixed solution containing nickel nitrate and copper nitrate, wherein the mass fractions of Ni and Cu are 2.0 wt% and 2.0 wt% respectively, taking 140 g of the mixed salt solution, and ultrasonicating it under 100 Hz ultrasonic conditions for 1 h to obtain a precursor mixed solution;
[0082] (3) Add the precursor mixture to the carrier dispersion, immerse at 4°C and 6Kpag for 2 hours, use 100Hz ultrasonic assistance, add a stream of nitrogen every 20 minutes to normal pressure, filter after immersion, and then calcine the obtained solid twice, the first calcination temperature is 200°C, the calcination time is 5 hours, the second calcination temperature is 500°C, the calcination time is 3 hours, all calcined in a nitrogen atmosphere, the heating rate is 5°C / min, to obtain a powder catalyst;
[0083] (4) Take 200 g of the powdered catalyst, add 6 g of carboxymethyl cellulose and 10 g of water, mix well, extrude into shape, and then perform secondary calcination. The primary calcination temperature is 200 ° C. and the calcination time is 5 h. The secondary calcination temperature is 380 ° C. and the calcination time is 3 h. Both calcinations are performed under a nitrogen atmosphere at a heating rate of 5 ° C / min to obtain catalyst D3#.
[0084] Application Example 1
[0085] This application example uses the following experimental conditions to evaluate the performance of each catalyst prepared in the above embodiments and comparative examples:
[0086] Before the experiment, the specific surface area and mechanical strength of each catalyst were measured (as shown in Table 1), and then the room temperature catalytic oxidation effect of VOCs waste gas (with butyl acetate as the characteristic pollutant) was tested (the oxidant was hydrogen peroxide as an example), specifically: the catalyst was placed in the room temperature catalytic oxidation fixed bed (reactor), the catalyst filling volume was 45mL, the VOCs waste gas was diluted with butyl acetate cylinder gas, the VOCs waste gas was passed into the reactor from bottom to top, the gas flow rate was 1.5L / min, 0.2% H2O2 solution was sprayed on the top of the reactor, the liquid flow rate was 3mL / min, and the VOCs concentrations at the outlet and inlet were detected after 2h of reaction. The treatment effect of the catalyst is shown in Table 1.
[0087] Table 1. Treatment effect of catalyst
[0088]
[0089] By comparing the test results of catalyst 3# and D1#, it can be seen that the catalytic oxidation effect of the catalyst without adding active components is poor, and the treatment efficiency is less than 30%, which is equivalent to the hydrogen peroxide oxidation treatment effect, proving that the active components can effectively improve the VOCs treatment efficiency.
[0090] Comparing the test results of catalysts 3# and D2#, it can be seen that the catalyst that was not impregnated under low-temperature vacuum conditions has poor dispersion of active metals, resulting in incomplete catalytic activity and poor treatment efficiency.
[0091] Comparing the test results of catalysts 3# and D3#, it can be seen that the efficiency of the catalyst that has not been modified by nitrogen and sulfur doping is equivalent to that of the modified catalyst in a short period of time, and long-term experimental investigation is needed.
[0092] Application Example 2
[0093] Catalysts 3# and D3# were used for long-term catalytic oxidation evaluation and comparison. The experimental conditions are as follows:
[0094] The catalyst was placed in a room temperature catalytic oxidation fixed bed (reactor) with a catalyst filling volume of 45 mL and a VOCs concentration of 300 mg / m 3 The butyl acetate waste gas was then passed into the reactor from bottom to top, with a gas flow rate of 1.5 L / min. A 0.2% H2O2 solution was sprayed on the top of the reactor, with a liquid flow rate of 3 mL / min. The VOCs concentration at the outlet and inlet was tested regularly. The experiment was carried out for 100 hours, and the results are shown in Table 2:
[0095] Table 2. Long-term experimental evaluation
[0096]
[0097] It can be seen from the results in Table 2 that after 100 hours of catalyst performance evaluation, the catalytic performance of catalyst 3# did not show any attenuation, the catalytic performance was stable, and the service life was long. The initial treatment effect of catalyst D3#, which was not modified by nitrogen and sulfur doping, was relatively stable. However, as the catalyst was used for a longer time, the performance of the catalyst suddenly changed at a certain point in time, and then the performance gradually decreased. The catalyst may have some active metal clusters and activated carbon sites occupied by VOCs. Therefore, the catalyst has better stability after nitrogen and sulfur doping modification, and can be used for the treatment of exhaust gas in extreme exhaust conditions such as sewage pools.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst for treating VOCs by catalytic oxidation at room temperature, comprising the following steps: 1) Grinding the activated carbon into fine powder and sieving it, adding the sifted powder into an alcohol solution, and ultrasonically treating it to obtain a carrier dispersion; 2) adding the 2-thiazolamine solution to the active metal salt solution and subjecting the solution to ultrasonic treatment to obtain a precursor mixed solution; 3) adding the precursor mixture to the carrier dispersion and impregnating the mixture at 0-5°C in vacuum, assisted by ultrasound, filtering after impregnation, and calcining in two stages to obtain a powder catalyst; 4) Adding a binder and water to the powder catalyst, mixing evenly, then extruding and calcining in two stages to obtain a room temperature catalytic oxidation catalyst; the active metal salt solution in step 2) is a nickel salt solution and a copper salt solution.
2. The preparation method according to claim 1, characterized in that The mesh size of the sieving in step 1) is 100 to 200 meshes, The alcohol solution is one or more of ethanol, ethylene glycol and propylene glycol, the mass ratio of the sieved powder to the alcohol solution is 1:(1-2), and the ultrasonic conditions of the ultrasonic treatment are: ultrasonic frequency is 80-120 Hz, and ultrasonic treatment time is 1-2h.
3. The preparation method according to claim 1, characterized in that: The nickel salt and the copper salt in step 2) are nickel nitrate, nickel chloride, copper nitrate and copper chloride.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass amount of the active metal salt solution in step 2) is 0.2-0.8 times the mass of the activated carbon fine powder; the concentration of the 2-thiazolamine solution is 1-2wt% in terms of nitrogen element.
5. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 3), the mass ratio of the precursor mixed liquid to the carrier dispersion liquid is (0.067-0.402):
1.
6. The preparation method according to any one of claims 1 to 3, characterized in that: Step 3) In the calcination process, the first calcination temperature is 150-250°C, the calcination time is 3-5h, the heating rate is 5°C / min, and the second calcination temperature is 450-650°C, the heating rate is 5°C / min.
7. The preparation method according to any one of claims 1 to 3, characterized in that: The mixing ratio in step 4) is the mass ratio of powder catalyst: binder: water = 1: (0.01-0.1): 0.
05.
8. The preparation method according to any one of claims 1 to 3, characterized in that: Step 4) The calcination atmosphere is an inert gas atmosphere, the calcination temperature in the first stage is 150-250°C, the calcination time is 3-5h, the heating rate is 5°C / min, and the second stage is 300°C-450°C, the heating rate is 5°C / min.
9. A catalyst for treating VOCs by catalytic oxidation at room temperature prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the catalyst for treating VOCs by catalytic oxidation at room temperature prepared by the preparation method according to any one of claims 1 to 8 in treating VOCs waste gas by catalytic oxidation at room temperature.
Citation Information
Patent Citations
Method for preparing dual-transition-metal-monoatom-loaded ACF catalyst for normal-temperature degradation of VOCs
CN108772067A
Preparation method of carbon-based composite material capable of catalytically degrading various organic matters at room temperature, and testing device
CN112108115A